2013
DOI: 10.1049/iet-pel.2012.0357
|View full text |Cite
|
Sign up to set email alerts
|

Methods of source current reference generation for predictive control in a direct matrix converter

Abstract: Rivera, M (Rivera, Marco). Univ Talca, Dept Ind Technol, Talca 747C, Chile.Two control strategies that allow the control of source and load currents for direct matrix converters are presented in this study. Both methods use the switching state of the converter in the subsequent sampling time, based on an optimisation algorithm given by a simple cost function and the discrete system model. The control goals include regulation of load currents according to an arbitrary reference and good tracking of the source c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 35 publications
2
48
0
Order By: Relevance
“…As reported in [25]- [28], [31], [33]- [36], [70] this strategy performs well with a very good behavior in both steady and transient state showing to be a very good alternative to classical control strategies. …”
Section: Principle Of Predictive Control In Mcssupporting
confidence: 66%
“…As reported in [25]- [28], [31], [33]- [36], [70] this strategy performs well with a very good behavior in both steady and transient state showing to be a very good alternative to classical control strategies. …”
Section: Principle Of Predictive Control In Mcssupporting
confidence: 66%
“…5 and in [15], [17], [23] demonstrate that by imposing a given waveform for the source current, it is possible to obtain a better performance than with an instantaneous reactive power minimization (Fig. 4), reducing the total harmonic distortion (THD) of both input and load currents.…”
Section: A Basic Current Controlmentioning
confidence: 95%
“…However, it has been observed that the PCC, using the reactive power minimization term, is very sensitive to the distortion of the source voltage and resonance of the input filter [16] (before =0.06[s]). By implementing active damping method (after =0.06[s]), it is possible to improve the performance of the system by mitigating the resonances of the input filter [16], [17]. It is also possible to force the source current to follow a sinusoidal reference value, regardless of the distortion level at the input side.…”
Section: A Basic Current Controlmentioning
confidence: 99%
See 2 more Smart Citations